Pengaruh Promosi, Inovasi, Dan Kualitas Produk Terhadap Kinerja Perusahaan Melalui Kepuasan Pelanggan Jahe Merah Laris Pisan - Muphimin; Zulkifli; Miranda, Agustinus (CV ODIS, 2023)
This study aims to analyze the direct and variable influence of promotion, innovation and product quality as well as indirect on company performance through customer satisfaction Red Ginger Laris Pisan. The research sample was 112 respondents who were existing customers and new customers. Data analysis techniques use Structural Equation Modeling (SEM) analysis processed with Smart-PLS software. The study’s results proved that the variables of promotion, innovation and product quality significantly affected customer satisfaction, and customer satisfaction significantly affected company performance. Meanwhile, product quality variables have a significant effect on company performance, but promotion variables and innovation variables do not have a significant effect on company performance.